Oppositional politics and the internet in Iran: A visual semiotic analysis of Iranian green movement‘s websites / Yousef Mostafalou - Yousef, Mostafalou (2016)

(untitled)
The new information and communication technologies, especially, the Internet as a contested terrain or site of struggle, have played an important role in the mediation of cultural and political struggles in Iran. The goal of the study is to illustrate ways in which the Internet is utilized by the Iranian Green Movement activists to advance their cultural and political struggles. To this end, the study focuses on how and whether the Internet has been used by the Iranian Green Movement activists for promotion of their political and cultural struggles with special attention on the cognitive function of the Internet on alternative forms of culture and information production for representation and reconstruction of collective identity, the logistic function of the Internet to increase public participation, organization and mobilization of protest, tactical function of the Internet for direct expression of their political struggles, and development of alliance and solidarity between movement activists to facilitate the movement‘s collective struggles against the Islamic Republic of Iran‘s theocratic state‘s oppressive policies. The thesis methodology deploys Roland Barthes‘s semiotic model for visual semiotic analysis of the website home pages and visual texts of the Iranian Green Movement. Roland Barthes‘s semiotics perspective has three levels of signification. The first (denotative) order of signification is seen as primarily representational and relatively self-contained. The second (connotative) order of signification reflects ―expressive‖ and cultural values that are attached to a sign. In the third (mythological or ideological) order of signification, the sign reflects major culturally variable concepts underpinning a particular worldview—such as Islamic domination, totalitarianism, dictatorship, tyrannies and violence, absolutism, Islamic sexual torture and violence and so on. The finding of the thesis shows the Internet contributes to different conditions that establish movement formation; promotion and dissemination of alternative forms of cultures, information, and meaning; representation and reconstruction of collective identity; and iv organization and mobilization of mass demonstrations, and direct expression of political struggles of oppositional movement activists. The thesis concludes that the Internet has been used by the Iranian Green Movement‘s activists for the promotion of their political interests and agendas, which contribute to a progressive cultural and political struggle that helps to reproduce their alternative form of cultures and identities and focus their political struggle while facilitating their oppositional political movements to seriously challenge the status quo culture and politics. But, the Iranian Green Movement activists do not used full potential of the Internet and websites for promotion of their political struggles.